2016
DOI: 10.1111/joic.12342
|View full text |Cite
|
Sign up to set email alerts
|

Transradial Versus Transfemoral Carotid Artery Stenting: A 16‐Year Single‐Center Experience

Abstract: The TR approach for CAS is safe and efficacious, with acceptable cross-over rate. In both groups, vascular complications rarely occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 11 publications
(29 reference statements)
0
38
0
1
Order By: Relevance
“…4 Ao-Om or IM count in the left radial group. 5 Ao-RCA (aorta to right coronary artery) graft count in the right radial group. 6 Ao-RCA count in the left radial group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Ao-Om or IM count in the left radial group. 5 Ao-RCA (aorta to right coronary artery) graft count in the right radial group. 6 Ao-RCA count in the left radial group.…”
Section: Resultsmentioning
confidence: 99%
“…In studies related to coronary angiography and percutaneous intervention that were conducted in recent years, transradial access has left its disadvantage in terms of time and performance relative to the transfemoral route, and advantageous in terms of complications [3][4][5] . Recently, radial access has been used for the purpose of carotid and renal artery angiography [6][7][8] , transradial access has been used for acute ischemic stroke intervention [9] , but femoral access is still advantageous from the point of view of the radiation exposure dose of the operator [10] .…”
Section: Introductionmentioning
confidence: 99%
“…A study from Argentina compared transradial vs transfemoral CAS[32]. A total of 775 consecutive patients undergoing CAS during 16 years were included (101 transradial vs 674 transfemoral).…”
Section: Head-to-head Comparison/combination Of Strategiesmentioning
confidence: 99%
“…Angiographic success was achieved in all 775 patients. There was a significant difference in cross-over rate (4.9% vs 0%, for the transradial vs the transfemoral approach, respectively; P < 0.05), but not in the incidence of in-hospital major adverse cardiac and cerebral events (2% vs 3.6%, for the transradial vs transfemoral approach, respectively; P = not significant)[32]. It was concluded that both approaches are safe and efficacious.…”
Section: Head-to-head Comparison/combination Of Strategiesmentioning
confidence: 99%
“…Аналогичная техника стентирования через ТР-доступ была адаптирована для лечения стенотических поражений каротидных артерий [5]. На сегодняшний день было проведено одно рандомизированное [8] и несколько нерандомизированных исследований по сравнению ТР-и ТФ-доступов при КС [9,10], однако ни одно из этих исследований не коснулось вопроса микроэмболических поражений головного мозга (ГМ) после процедуры, выявляемых на диффузионно-взвешенной магнитно-резонансной томографии (ДВ МРТ).…”
Section: Introductionunclassified